Pemanfaatan Rapor Pendidikan Pada Pengembangan Program di SDN Puncak 2 - Rubiherlan, Yusuf; Pristi, Marlin; Nursanti, Funny Eka; Handayani, Sri; Muchtar, Hendi S. (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract: School is a means of implementing the educational process. As formal educational organizations, schools have a responsibility to improve the quality of education. To guarantee the quality of education, in line with the Minister of National Education Regulation number 19 of 2007 concerning education management standards by primary and secondary education units, education can be said to have an achievement process if it is able to guarantee the quality of education by increasing the intelligence of the nation's life. The meaning of educational report cards is able to describe the condition of educational units throughout Indonesia. To find out how much impact educational report cards have on school development, it is necessary to conduct research on the indicators that influence them. The aim of this research is to find out to what extent the education report card policy helps the program development process at SDN Puncak 2. This research uses qualitative methods where answering problems requires in-depth understanding in the context of time and situation. The data analysis technique in this research uses several techniques, namely observation, interviews and documentation. The instrument used was an interview sheet which consisted of several structured questions related to the researchKey Words: Utilization, Educational Reports, DevelopmentAbstrak: Sekolah adalah sarana dalam pelaksanaan proses pendidikan. Sebagai organisasi pendidikan formal, sekolah memiliki tanggung jawab dalam meningkatkan mutu pendidikan. Untuk menjamin mutu pendidikan tersebut, maka sejalan dengan peraturan menteri pendidikan nasional nomor 19 tahun 2007 tentang standar pengelolaaan pendidikan oleh satuan pendidikan dasar dan menengah maka pendidikan dapat dikatakan memiliki proses pencapaian jika mampu menjamin mutu  dengan meningkatkan kecerdasan kehidupan bangsa. Pemaknaan raport pendidikan mampu menggambarkan kondisi satuan pendidikan di seluruh Indonesia Untuk mengetahui seberapa berdampaknya Raport Pendidikan terhadap pengembangan sekolah maka perlu dilakukan penelitian tentang indikator-indikator yang mempengaruhinya. Adapun tujuan dari penelitian ini adalah untuk mengetahui sejauh mana kebijakan rapor pendidikan membantu proses pengembangan program di SDN Puncak 2. Penelitian ini menggunakan metode kualitatif dimana untuk menjawab permasalahan memerlukan pemahaman mendalam dalam konteks waktu juga situasi. Tekhnik analisa data dalam penelitian ini menggunakan beberapa tekhnik yaitu observasi, wawancara dan dokumentasi. Instrumen yang digunakan adalah lembar wawancara yang didalamnya terdiri dari beberapa pertanyaan terstruktur yang berkaitan dengan penelitian.Kata Kunci: Pemanfaatan, Raport Pendidikan, Pengembangan